Excess Words, Surplus Names: Rancière and Habermas on Speech, Agency, and Equality - Michael Feola (Journal of French and Francophone Philosophy, 2019)
Jürgen Habermas and Jacques Rancière treat speech as the medium for politics and, likewise, both diagnose the pathologies that follow from blockages on civic speech.  That said, these broad commonalities give rise to significant divides regarding the social ontology of language, the forms of power that attend linguistic exchange, and how speech informs democratic agency. Ultimately, the essay will argue that Rancière highlights the political deficits within deliberative commitments to democratic values. In doing so, his challenge yields broader insights for a democratic politics of speech and the linguistic resources that facilitate such a politics.